2011
DOI: 10.1016/j.toxlet.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal expression of MAPK, EGFR, CK17 and TGk in the skin lesions of chloracne patients exposed to dioxins

Abstract: a b s t r a c tObjective: Chloracne is one of the most sensitive and specific hallmark of dioxin intoxication. Although its clinical features are clearly described, poor understanding of the molecular pathways of dioxin-induced chloracne hampers a rational approach to therapy. The aim of the present study was to investigate the role of EGFR, MAPK, CK17, and TGk in the pathogenesis of chloracne related to dioxin exposures. Methods: Epidermal tissues of twelve chloracne patients exposed to dioxins were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The reduced number of sebaceous glands and sebocytes may be associated with the altered metabolism of the mature sterol-binding protein (mSREBP-1), resulting from AMP-activated protein kinase (AMPK) activation [155]. On the other hand, the MAPK signaling pathway is also crucial for skin lesion formation in chloracne patients, as AhR activation in chloracne induces the activation of EGFR and MAPK [156]. EGFR and AhR compete for common coactivator p300 for their transcriptional activity.…”
Section: Skin Appendage Disorder: Chloracnementioning
confidence: 99%
“…The reduced number of sebaceous glands and sebocytes may be associated with the altered metabolism of the mature sterol-binding protein (mSREBP-1), resulting from AMP-activated protein kinase (AMPK) activation [155]. On the other hand, the MAPK signaling pathway is also crucial for skin lesion formation in chloracne patients, as AhR activation in chloracne induces the activation of EGFR and MAPK [156]. EGFR and AhR compete for common coactivator p300 for their transcriptional activity.…”
Section: Skin Appendage Disorder: Chloracnementioning
confidence: 99%
“…In addition to the acceleration of keratinization, an immunohistological study revealed an activation of EGFR in chloracne [79]. AMP-activated protein kinase (AMPK) is activated by AHR and downregulates protein turnover of the mature sterol regulatory element-binding protein (mSREBP-1), leading to a decrease in the size of sebaceous glands and the number of sebocytes within each gland in the skin [80].…”
Section: Chloracne Caused By Environmental Ahr Ligandsmentioning
confidence: 99%
“…Also, individuals with chloracne had abnormal levels of keratin 17 in the epidermis and abnormal levels of glutamine enzyme gene and protein. These findings suggested that normal proliferation and differentiation of cells were altered and led to the development of chloracne (Liu et al, 2011).…”
Section: Discussionmentioning
confidence: 96%